(untitled) (Ustozlar uchun, 2026)
This article examines modern principles of assessment and evaluation in English Language Teaching (ELT), emphasizing learner-centered approaches that support language development rather than mere testing. It discusses formative and summative assessment, alternative assessment methods, and the role of feedback in improving learners’ communicative competence at A2–B1 level. The study highlights how fair, transparent, and skill-integrated assessment practices enhance motivation, autonomy, and overall learning outcomes in secondary education.